Radioactive Iodine-125 in Tumor Therapy: Advances and Future Directions - Wei, Shuhua; Li, Chunxiao; Li, Mengyuan; Xiong, Yan; Jiang, Yuliang; Sun, Haitao; Qiu, Bin; Lin, Christopher J.; Wang, Junjie (Frontiers in Oncology, 2021)
Radioactive iodine-125 (I-125) is the most widely used radioactive sealed source for interstitial permanent brachytherapy (BT). BT has the exceptional ability to deliver extremely high doses that external beam radiotherapy (EBRT) could never achieve within treated lesions, with the added benefit that doses drop off rapidly outside the target lesion by minimizing the exposure of uninvolved surrounding normal tissue. Spurred by multiple biological and technological advances, BT application has experienced substantial alteration over the past few decades. The procedure of I-125 radioactive seed implantation evolved from ultrasound-guidance to computed-tomography guidance. Compellingly, with the creative introduction of 3D-printed individual templates, BT-treatment planning systems and artificial intelligence navigator systems remarkably increased the accuracy of I-125 BT and individualized I-125 ablative radiotherapy. Of note, utilizing I-125 to treat carcinoma in hollow cavity organs was enabled by the utility of self-expandable metal stents (SEMS). Initially, I-125 BT was only used in the treatment of rare tumors. However, an increasing number of clinical trials upheld the efficacy and safety of I-125 BT in almost all tumors. Therefore, the aim of this study is to summarize the recent advances of I-125 BT in cancer therapy, which covers experimental research to clinical investigations, including the development of novel techniques. This review also raises unanswered questions which may prompt future clinical trials and experimental work.